A bibliometric analysis of corporate sustainability performance: current status, development and future trends - Gardazi, Syeda Saba Nazir; Sheikh Hassan, Ahmad Fahmi; Bello, Mohammed Sabo (Logos University International, Florida, United States of America, 2023)
Purpose: This study aimed to focus on bibliometric analysis and the concept of corporate sustainability performance (CSP) to understand the evolutionary and developmental trends in the field of CSP. Design/methodology/approach: This study conducted a bibliometric analysis of 1,518 Scopus-indexed documents on CSP published from 1975 to August 2021 to provide meaningful insights for further discussions. For this purpose, the study used VOSviewer software for drafting the literature and Harzing's Publish or Perish software to obtain impact matrices and citation information. Findings: The findings revealed that the number of CSP-related publications has increased in recent years (1975-1991: 21 publications, 1992-2007: 206 publications, and 2008-2021: 1291 publications). Furthermore, the findings revealed a significant increase in interest in the CSP field. Business, management, and accounting (34 %) were the most studied subject areas, and the Journal of Business Ethics, with a TP of 150, as the most productive scientific journal. Research, Practical & Social implications: This study examines how academic interest in CSP has evolved and identifies areas for further exploration in the CSP context. This study contributes to the current literature in the CSP domain by providing a bibliometric analysis. Furthermore, this bibliometric analysis would aid in decision-making and policy formulation related to CSP. Originality/value: The overall findings revealed an increase in CSP development in the scientific field, linked to the continued expansion of empirical research papers, researchers/authors, and citations.